A Management and Economic Survey in Implementation of Blown Bitumen Production Using Acidic Sludge Recycling (A Case Study) - Malek Hassanpour (Iranian Journal of Health, Safety and Environment, 2016)
Many units of blown bitumen and used-motor oil reprocessing industries have been currently implemented and many modern technologies and additives are being developed and requested continuously. The objective of current study was a management and economic survey in implementation of blown bitumen production using acidic sludge recycling as a new additive that encompasses financial views and other success factors so carried out using a Kanji's Business Excellence Model, empirical equations, professional experiences and observations during establishment an industry. Using acidic sludge had promoted the product quality in parallel with the TQM parameters. Current study had shown the indices values such as value-added percent, profit, annual income, breakeven point, value-added, output value, data value, variable cost of commodity unit and production costs were found to be about 44%, $ 5308605.14, $ 5252251.65, $ 1183.67 , $ 5401935.47, $ 6748064.5, $ 12150000, $ 140.93 and $ 6897748.4 respectively. The breakeven point about 2.46%, time of return on investment about 0.07, BES about 800.2 (for KBEM) and 806.77 (for EFQM) was represented a systematic practice so that thrift outlays and boost the strength and weakness points to improve.